Homo holocaustus, czyli holocaustowe doświadczenia autobiograficzne kobiet - Żórawska, Natalia (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
The aim of this paper is to depict the motif of Extermination in autobiographical women’s prose after 2000. The paper demonstrates that in recent years more and more authoresses of the second and third post-Holocaust generation have been writing down their traumatic experiences and the reason for this lies in the social stigmatization of Jewish people. It is stressed in the paper that the Holocaust issues are part and parcel of a cultural taboo and – similarly to women’s prose – they are frequently ignored or evaluated negatively. The Holocaust issues are tackled by contemporary young writers of Jewish descent who – contrary to the authors of the previous generation – did not experience the mass murder of Jews; however, they feel its effects today. The paper proves that in Poland we fail to carry out research on trauma studies, and devoting attention to the woman’s viewpoint is very rare. The quoted examples from the autobiographical novels written by Ewa Kuryluk, Agata Tuszyńska, Roma Ligocka and Magdalena Tulli show that this kind of writing is becoming more and more important within the literature focused on annihilation. In comparison with the autobiographical works of Marek Bieńczyk, Jan Tomasz Gross and Michał Głowiński, the women’s holocaust stories are distinguished by authenticity, emotionality, intimacy and honesty of narration. The stories are devoid of pathos and they highlight the figure of a mother. Moreover, the confessions are based on the physical feeling of a legacy which has remained in their hearts and minds after the trauma their loved ones had to experience. We attempt to describe post-Holocaust women’s prose in comparison with Jewish literature in Poland as well as draw the reader’s attention to the characteristic features of these issues in comparison with the autobiographical works by men.
Homo holocaustus – holocaust autobiographic experiences of women
Keywords: zagłada; kobiety; autobiografizm; proza kobieca; extermination; women; autobiographism; women’s prose